Hybrid TiO2/graphene derivatives nanocomposites: is functionalized graphene better than pristine graphene for enhanced photocatalytic activity?. Issue 6 (9th March 2017) - Yang, Yin-Cai; Huang, Wei-Qing; Xu, Liang; Hu, Wangyu; Peng, P.; Huang, Gui-Fang
Abstract : Graphene (GR) and its derivatives are generally assumed to be electron shuttles in order to explain the improved photocatalytic activity of their nanocomposites (such as TiO2 /GR). Abstract : Graphene (GR) and its derivatives are generally assumed to be electron shuttles in order to explain the improved photocatalytic activity of their nanocomposites (such as TiO2 /GR). However, it fails to account for the experimental results, which demonstrate that the photocatalytic activity of TiO2 /reduced graphene oxide (RGO) is higher than that of TiO2 /GR. Herein, we explore the underlying mechanism for the enhanced photocatalytic activity of TiO2 /RGO (GR) by comparing several influential factors: band gap, band alignment near the gap, optical absorption, and active sites, via first-principles calculations. The results show that the small band gap, the type-II staggered band alignment, and the negatively charged O atoms as active sites in photocatalytic reactions are likely to be key factors for the photocatalytic activity of TiO2 /RGO being better than that of TiO2 /GR, partly offering a physical interpretation for related experimental results. Interestingly, the enhanced photocatalytic activity of TiO2 /graphane (GRH) is also predicted. These results suggest that functionalized GR is most likely better than pristine graphene at improving the photocatalytic activity of TiO2 /GR-based semiconductor photocatalysts.